Virtual Art and its Impact on Spirituality - Usanova Umida Ubaydulla qizi (International Journal on Integrated Education, 2022)
The article discusses the positive and negative effects of virtual art on the spirituality of young people. It also focuses on aspects that require attention, taking into account the external influences on the upbringing of young people and the formation of their spiritual world.